Anticoagulation in Behçet related intrathoracic vasculitis. (2018) - Nokes, Brandon; Tseng, Andrew S.; Cartin-Ceba, Rodrigo; Shamoun, Fadi; Jokerst, Clinton; Mertz, Lester
Abstract: Behçet disease is a rare multisystem condition associated with HLA-B51 positivity that commonly afflicts individuals of Turkish or Middle Eastern descent, less than 10% of whom have pulmonary involvement. Behçet-related pulmonary vasculitis is an uncommon and heterogeneous group of conditions, often with associated pulmonary artery thrombus formation. These microthrombi can result in a misdiagnosis of acute pulmonary embolism. Anticoagulation therapy can be difficult, as blood thinners increase the risk of pulmonary hemorrhage without affording the same benefits as in pulmonary embolism management. We present two cases of pulmonary vasculitis in the context of Behçet's syndrome, one in a Native American man with associated superior vena cava syndrome and pericarditis, with an increased risk of hemorrhagic pericardial effusion, and the other in an African American man with acute hypoxic respiratory failure with an increased risk of alveolar hemorrhage. We describe their management and the balancing act surrounding anticoagulation therapy in Behcet-related pulmonary vasculitis.